GENERAL PROBLEMS OF TRANSLATION THEORY - Tursunova Farangiz Dildorbekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The theory of translation is often subdivided into general, special and particular theories of translation. The general theory of translation should apparently be engaged in the study of the “essence” of translation, which is characteristic of all types and subtypes (types and subspecies) of translation (written; oral; simultaneous, consecutive by ear and from a sheet; one-sided, two-sided; scientific and technical, official business, military, socio-political, artistic, cinematographic, etc.) from any language to any other.